Jordanian parental perception of screen time and its association with psychological distress: A cross-sectional design - Jehad Feras AlSamhori; Ahmad A. Toubasi; Dunia Z. Jaber; Hadeel H. Ghanem; Bayan I. Thainat; Ahmad Feras AlSamhori; Heba Kalbouneh (Pediatrics and Neonatology)
Background: The excessive use of electronic devices among children is a global concern because of its negative impact on behavior. This cross-sectional study aimed to assess parents' awareness of their children's electronic device use and their perspective on how screen time affects behavior for 4–10-year-olds in Jordan. Methods: A cross-sectional study was conducted to assess parents' awareness of their children's electronic device usage. The study included 807 mothers and fathers from Jordan with at least one child aged 4 to 10. The data collection instrument consisted of a self-administered survey with 43 questions, including sociodemographic characteristics and the Strength and Difficulties Questionnaire. Descriptive analysis, categorical Chi-square test, Independent t-test, and Mann-Whitney U test were used for statistical analysis. The study followed ethical standards and principles. Results: A survey of 807 parents in Jordan found that gaming and videos were the most common content watched by children, and 61.3% used devices alone. Only 37.1% of parents believed that device use could improve their children's psychological growth, while 72.7% and 65.9% believed it could impact negatively their children's mental and psychological growth, respectively. The Strengths and Difficulties Questionnaire showed that 51.4% of children were normal, while 25.3% were borderline and 23.3% were abnormal. Conclusion: Children in the study used electronic devices excessively and this was linked to severe behavioral problems. Parents should follow AAP guidelines and spend more time with their children through non-electronic activities to improve their behavior.